2015
DOI: 10.1016/j.patcog.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy human motion analysis: A review

Abstract: Human Motion Analysis (HMA) is currently one of the most popularly active research domains as such significant research interests are motivated by a number of real world applications such as video surveillance, sports analysis, healthcare monitoring and so on. However, most of these real world applications face high levels of uncertainties that can affect the operations of such applications. Hence, the fuzzy set theory has been applied and showed great success in the recent past. In this paper, we aim at revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 234 publications
0
20
0
1
Order By: Relevance
“…In their survey, it was shown that methods exploiting semantic information yield superior performance compared to their nonsemantic counterparts in many scenarios. Human action recognition in still images is also discussed within the context of fuzzy domain in a recent survey [34].…”
Section: Related Workmentioning
confidence: 99%
“…In their survey, it was shown that methods exploiting semantic information yield superior performance compared to their nonsemantic counterparts in many scenarios. Human action recognition in still images is also discussed within the context of fuzzy domain in a recent survey [34].…”
Section: Related Workmentioning
confidence: 99%
“…Anger has the emotion recognized with highest accuracy. [9] and multimodal fusion [3,4]. Castellano et al [7] extended their work to multimodal framework integrating face-expression, body-gestures, and speech.…”
Section: Implementing Emotional Phrase Matchingmentioning
confidence: 99%
“…Walking, running, lifting, and jumping are the most common human movements in daily life [1]. Consequently, controlling, understanding and recognizing human movements are important tasks for people in the fields of robotics, computer vision, ergonomics, and biomechanics [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%